Accelerated ash accumulation method for diesel particulate filter and its characterization: a review. Issue 7 (27th May 2020) - Zheng, Zuwei; Su, Sheng; Zhan, Reggie; Lin, He; Wang, Yinan; Zhao, Xuteng
ABSTRACT: It is well known that high-efficiency wall-flow particulate filter is the most commonly used technology that can effectively reduce both particulate matter (PM) and particulate number (PN) to comply with the latest emission legislations. Ash, defined as the noncombustible, non-evaporative residue derived mostly from lubricants, has critical impact on engine backpressure, particulate filter filtration efficiency and durability performance, therefore, the investigation of ash impact on particulate filter is of great importance. Due to cost-saving potential, several published methods from different laboratories for accelerated ash loading under carefully controlled conditions are described in this review, including some characterization methods that have been used for the evaluation of filter performance. In addition, the impact of ash deposit on back pressure and regeneration performance are also discussed in this review.